Designing and assessing a course on prioritization and importance assessment in strategic non-routine requirements engineering processes. Issue 4 (November 2016) - Heerkens, Hans; Wegen, Leo; Heijden, Beatrice
Abstract In this contribution, we present a course for making stakeholders in requirements engineering (RE) processes aware of the relevance of importance assessment (the thinking process that they go through while assessing requirement weights) and giving them some experience with specific aspects of the importance assessment process. We also analyze the experiences of the participants in five pilot sessions. In RE instruments, elicitation of requirement weights receives much attention. However, the processes that individual stakeholders go through while assessing weights are largely ignored or seen as a 'black box'. In the course, participants gain experience with some common issues and pitfalls in assessing weights. Issues covered are: completeness and interdependence of requirements, causal relationships and the common denominator, handling 'irrational' requirements, and the meaning of 'importance' (priority). The course was given in various large organizations in the aerospace sector, and data on participants' experiences were gathered by means of a standardized questionnaire. The extent to which the participants claimed they learned about the relevance of importance assessment and about how to perform it were, respectively, 2.89 and 2.72 on a scale from 1 to 5. The relevance of the various assignments was rated between 3.74 and 4.00 on a 1–5 scale. Our study indicates that the course, or elements of it, should be embedded in an organization's work practices in order to achieve lasting effects.